Learn If Sx 2x2 3x 4 And Tx X 4 Then Sx Tx

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# If s(x) = 2x^{2} + 3x - 4, and t(x) = x + 4 then s(x) · t(x) = ?

We will use the concept of functions to solve this.

## Answer: If s(x) = 2x^{2} + 3x - 4, and t(x) = x + 4 then s(x) · t(x) = 2x^{3} + 11x^{2} + 8x - 16.

Let us solve it step by step.

**Explanation:**

Given:

s(x) = 2x^{2} + 3x - 4

t(x) = x + 4

Both s(x) and t(x) are functions of x and dependent on x.

s(x) · t(x) = (2x^{2} + 3x - 4)(x + 4)

= 2x^{3} + 3x^{2} - 4x + 8x^{2} + 12x - 16

= 2x^{3} + 11x^{2} + 8x - 16

### Thus, if s(x) = 2x^{2} + 3x - 4 and t(x) = x + 4 then, s(x) · t(x) = 2x^{3} + 11x^{2} + 8x - 16.

Math worksheets and

visual curriculum

visual curriculum